Snout mites from caves in Brazil, with description of a new species (Acari: Trombidiformes: Bdellidae) - Hernandes, Fabio Akashi [UNESP]; Bernardi, Leopoldo F. de O.; Ferreira, Rodrigo L. (Taylor & Francis Ltd, 2011)
In this paper we describe the first species of the genus Cyta from Brazil, Cyta troglodyta sp. nov., with a key to the world species of the genus. New records of mites of the family Bdellidae are reported from caves in Brazil.
Keywords: Acari; Bdellidae; Cyta; snout mites; cave; Brazil